Impact of block sequence on the phase morphology of multiblock copolymers obtained by high-throughput robotic synthesis. (15th January 2021) - Behl, Marc; Balk, Maria; Lützow, Karola; Lendlein, Andreas
Graphical abstract: A library of well-defined MBCs composed of two different hydrophobic, crystallizable blocks providing domains with well-separated melting temperatures ( T m s) were synthesized from the same type of precursor building blocks as strictly alternating (MBCsalt ) or random (MBCsran ) MBCs and compared. Highlights: Synthesis of multiblock copolymers using automated robotic synthesizer. Multiblock copolymers with random and strictly alternating sequence of segments. T m s associated to melting of OCL and OTHF domains were almost not affected by sequence of segments. Elongation at break in MBCsalt was reduced almost by a factor of 2 compared to MBCsran . Abstract: The chemical nature, the number length of integrated building blocks, as well as their sequence structure impact the phase morphology of multiblock copolymers (MBC) consisting of two non-miscible block types. We hypothesized that a strictly alternating sequence should favour phase segregation and in this way the elastic properties. A library of well-defined MBCs composed of two different hydrophobic, semi-crystalline blocks providing domains with well-separated melting temperatures ( T m s) were synthesized from the same type of precursor building blocks as strictly alternating (MBCsalt ) or random (MBCsran ) MBCs and compared. Three different series of MBCsalt or MBCsran were synthesized by high-throughput synthesis by coupling oligo( ε -caprolactone) (OCL) of different molecular weights (2, 4, and 8 kDa) with oligotetrahydrofuran (OTHF, 2.9 kDa) via Steglich esterification in which the molar ratio of the reaction partners was slightly adjusted. Maximum of weight average molecular weight ( M w ) were 65, 000 g∙mol −1, 165, 000 g∙mol −1, and 168, 000 g∙mol −1 for MBCsalt and 80, 500 g∙mol −1, 100, 000 g∙mol −1, and 147, 600 g∙mol −1 for MBCsran . When M w increased, a decrease of both T m s associated to the melting of the OCL and OTHF domains was observed for all MBCs. T m (OTHF) of MBCsran was always higher than T m (OTHF) of MBCsalt, which was attributed to a better phase segregation. In addition, the elongation at break of MBCsalt was almost half as high when compared to MBCsran . In this way this study elucidates role of the block length and sequence structure in MBCs and enables a quantitative discussion of the structure-function relationship when two semi-crystalline block segments are utilized for the design of block copolymers.